STUDY OF TaSOS4 GENE AND YIELD , CHEMICAL TRAITS IN SOME BREAD WHEAT GENOTYPES UNDER SALINITY CONDITIONS - & et al., AL-Salihy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This experiment was carried out at greenhouse in Centre of Biotechnology Researches/ University of Nahrin using soil clay loam texture, soil was in pots closed to study the effect of different salinity levels on detection TaSOS4 gene and yield traits in some bread wheat genotypes (Triticum aestivum L.).Wheat seeds were planted in Nov. 2016 with ten seeds in each pot. a factorial experiments within Randomized Complete Block Design with three replications was used and Four levels of salinity (4, 8 , 12 and 16 ds.m-1) with four genotypes (G1:Iraq, G2: 2H ,G3: 3H and G4: Hussein). The result showed non-significant differences among genotypes under first salinity levels (4 ds.m-1) in most traits. in second salinity level (8 ds.m-1), G2,G4 gave variation on G1 over 10 in No. grains. Spike-1 , 5-10 in grain 1000weight , over 2% in percentage of protein and K+/Na+ ratio value over 7. in third salinity level (8 ds.m-1), G2,G4 gave variation on G1 over 25 in No. grains. Spike-1, over 12 in grain 1000weight, over 100% in plant grains yield , 2-3% in percentage of protein , over 5 in K+/Na+ ratio value . in forth salinity level (16 ds.m-1), G2 gave variation on G1 over 25 in No. grains. Spike-1 , over 14 in grain 1000weight, over 100% in plant grains yield, over 3% in percentage of protein , over 5 in K+/Na+ ratio value. Molecular study showed TaSOS4 gene was found in G2 ,G3 and G4 genotypes but it did not appear in G1 genotype. This indicator refers to differences among genotypes in salinity tolerance and sensitive to salinity in G1 genotype.